Difficulties of Using the Interactive Whiteboard in Teaching Students who Face Learning Difficulties from the Point of View of Teachers in some Schools in the Hashemite Kingdom of Jordan - Abu Nowwas, Mousa Kh. (Dirasat: Educational Sciences, 2020)
This study dealt with the reality and obstacles of using the interactive whiteboard from the point of view of teachers who teach students with learning difficulties in some schools in the governorates of the Kingdom of Jordan. This study aimed to reveal the reality of using interactive by teachers of learning difficulties in some governorates of the Kingdom in teaching students of learning difficulties, to identify the obstacles that face the teachers of learning difficulties in some governorates of the Kingdom to use interactive whiteboard in teaching, explaining the importance of using the interactive whiteboard for teachers of learning difficulties in some governorates of the Kingdom to teach students of learning difficulties. Questionnaire was conducted with the assistance of some male and female teachers in this sector, and the results showed that the most obstacles are the ignorance of some teachers to this board in addition to the material conditions that do not allow the purchase of this method, in addition to that there are no specialists, whether trained or teachers in this field. Among the most t recommendations that were reached was to provide teachers with all the knowledge and skills related to technological innovations, especially the interactive whiteboard, and their use in the educational process, to provide teachers with all the knowledge and skills during the service, doing training courses for teachers and teachers of difficulties and many other recommendations that will be referred to later.